Predictors of food addiction symptoms among Malaysian university students - Cheah, Mun Hong Joseph; Chin, Yit Siew (Elsevier BV, 2024)
Objective: University students are susceptible to hyperpalatable food consumption, which may contribute to the development of food addiction. However, there is limited research on food addiction among Malaysian university students. This study aimed to investigate the prevalence of food addiction, as well as the factors that predicted food addiction symptoms among students in a selected local public university in Malaysia. Methods: This is a cross-sectional study whereby a total of 295 Malaysian university students were recruited from a selected local university. Participants were assessed through self-administered questionnaires and measured for their body compositions. Results: Findings revealed that 15.9% of the university students were at risk of having food addiction, with an average of 3.21 ± 1.62 food addiction symptoms. Multiple linear regression analysis indicated that binge eating (B = 0.086, p < 0.001) and anxiety (B = 0.071, p < 0.001), as well as high daily carbohydrate intake (B = 0.002, p = 0.004) significantly predicted food addiction symptoms (R2 = 0.346, F(3, 285) = 50.195, p < 0.001). Conclusions: Approximately one in five university students was at risk of food addiction. Moreover, higher levels of binge eating and anxiety, along with increased consumption of carbohydrates contributed to elevated food addiction symptoms. Effective intervention should be formulated based on the psychological and dietary aspects to tackle the food addiction problems among university students.